Viral load of patients with hantavirus pulmonary syndrome in Argentina - Bellomo, Carla María (2015)
Hantavirus causes severe illness including pneumonia, which leads to hospitalization and often death. At present, there is no specific treatment available. The hantavirus pathogenesis is not well understood, but most likely both virus‐mediated and host‐mediated mechanisms, are involved. The aim of this study was to correlate viral load in samples of hantavirus pulmonary syndrome cases and hantavirus infected individuals, with clinical epidemiological parameters and disease outcome. The variables that could potentially be related with viral load were analyzed. The retrospective study included 73 cases or household contacts, with different clinical evolution. Viral load was measured by reverse‐transcription and real time polymerase chain reaction. There was no statistically significant association between blood viral RNA levels and severity of disease. However, viral load was inversely correlated with IgG response in a statistically significant manner. The level of viral RNA was significantly higher in patients infected with Andes virus South lineage, and was markedly low in persons infected with Laguna Negra virus. These results suggest that the infecting viral genotype is associated with disease severity, and that high viral load is associated with a low specific IgG response. Sex, age and disease severity were not related with viral load. Further investigations increasing strikingly the number of cases and also limiting the variables to be studied are necessary.